Delivering Trauma-Informed Care in a Hospital Ward for Older Adults With Dementia: An Illustrative Case Series - Couzner, Leah; Spence, Natalie; Fausto, Karina; Huo, Yan; Vale, Lynn; Elkins, Samantha; Saltis, Johanna; Cations, Monica (Frontiers in Rehabilitation Sciences, 2022)
Introduction Up to 70% of older adults have experienced a psychologically traumatic event in their life. Traumatic events can have lifelong effects on functioning and emotion regulation and can affect behaviour and experiences in care settings. Common healthcare practices and environments can be re-traumatising for survivors. These features may trigger behaviour change (e.g aggression and agitation) particularly after the onset of dementia. However, very little research exists to understand how the effects of traumatic events manifest in aged care settings. Trauma-informed care is a framework in which the potential impact of trauma is acknowledged, and practices and procedures are adapted to maximise feelings of control and safety for the patient. Trauma-informed care is an innovative approach with little published evidence in acute geriatric settings. Methods We present a series of cases to demonstrate how psychological trauma can affect the experience of inpatient care for older people. The cases detail the patients’ relevant background, triggers and behaviours followed by the steps taken by staff to support the patient and respond to their trauma-related needs. These cases describe how the principles of trauma-informed care can be applied to recognise when past psychologically traumatic events are impacting the older adult in hospital. The outcomes of these interventions are reported on in terms of their impact on challenging behaviour, patient experiences and satisfaction with care, and/or staff confidence and skill. Findings A range of past events negatively impacted the patients during their time in hospital, including childhood abuse, military service, and domestic violence. Staff implemented strategies to accommodate trauma-related needs while providing care that improved safety and reduced patient distress. Principles of trauma-informed care were applied where able, including providing choices and enabling autonomy. However, organisational and environmental features of inpatient wards continued to pose risks for re-traumatisation. Conclusions Trauma-informed care is an under-utilised yet potentially beneficial approach to care for older adults in the hospital setting. The cases detailed here demonstrated that the impact of psychological trauma requires an individualised response from staff which when effectively implemented can promote staff and patient safety, reduce the risk of re-traumatisation, and minimise adverse events.